QUANTITATIVE ANALYSIS OF GENERIC AND BRANDED NAME AMPICILLIN IN TABLETS USING HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) - Putra, Effendy De Lux (INDONESIAN JOURNAL OF PHARMACY, 2002)
The determination of ampicillin in tablets of branded and generic names by reversed phase high performance liquid chromatography (HPLC) had been carried out. Using column selectosphere C18 (25cm x 4,6 mm) as stationary phase; water : acetonitrile : potassium phosphate 1 M : acetic acid 1 N (909+80+10+1) V/V as mobile phase; flow rate = 2,5 ml/minute; sensitivity = 0,08 AUFS and uv detector at 254 nm wave length. Identification of ampicillin BPFI, ampicillin (Pharos), and ampicillin in tablets of branded and generic names got the retention time 5 minutes.Determination of calibration curve linearity showed a linear correlation between the peak area versus concentrations from 200 to 700 ïg/ml with the correlation coefficient, r = 0,9984 and got the equation of regression Y = 249,89 X - 4305,15. The recovery test of ampicillin (Pharos) showed the concentration 99,36%ï£ïï£104,76% with deviation standard = 1,6447; relative error = 2,06% and coefficient of variation = 1,61%. The quantification of ampicillin in tablets with generic names showed the concentration = 99,69%ï£ïï£104,99% (PT. Indofarma); 91,03%ï£ïï£97,53% (PT. Phapros); 95,70%ï£ïï£102, 44% (PT. Farma); and for tablets of branded names namely : Binotal (PT. Bayer) = 93,38%ï£ïï£99,44%; Kalpicillin (PT. Kalbe Farma) = 91,41%ï£ïï£97, 95%; Parpicilin (PT, Prafa) = 97,19%ï£ïï£101,67% and Cetacilin (PT. Soho) = 95,60%ï£ïï£98,58%. All samples fulfilled the requirement of Farmakope Indonesia fourth edition (1995) namely containing ampicillin not less than 90,0% and not more than 120,0% from the label declared.Key words : HPLC, Ampicillin, assay